The Influence of Advertising, Trust, and Word of Mouth on the Investment Decision of Government Sukuk - Febrina, Lis; Nurwahidin (Formosa Journal of Sustainable Research, 2024)
This study analyzes the effects of advertising, trust, and word of mouth on the investment decisions of Government Sukuk. The population in this study are Government Sukuk investors. Based on the Hair formula, 115 respondents made up the sample. The sample research approach combines a purposive sampling strategy with a non-probability sampling technique. A questionnaire research instrument is used in a survey as part of the data collection process. techniques for partial least squares data processing. This research demonstrates that advertising has a positive and significant effect on investment decisions, trust has a positive and significant effect on investment decisions, and word of mouth has a positive and significant effect on investment decisions